2010
DOI: 10.1002/prep.200900092
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation between Electric Spark Sensitivity of Polynitroaromatic Compounds and Their Molecular Electronic Properties

Abstract: In this paper, a relationship between electric spark sensitivity and molecular electronic properties is studied for polynitroaromatic compounds. The lowest unoccupied molecular orbital energy and the Mulliken charges of the nitro group, and the number of the aromatic rings as well as certain substituted groups attached to the aromatic ring can be used for the prediction of the electric spark sensitivity. Electric spark sensitivities calculated by such a correlation are reasonably close to the experimental data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…It was indicated that experimental values of electrostatic sensitivity of energetic materials depend on various factors such as granulometry and particle shape [36,37], moisture content [36], the molecular electronic properties [38], the configuration of electrodes [38][39][40], and the general structure of the circuit [36]. As seen in Table 4, the predicted electrostatic sensitivities for the compounds are consistent with their impact sensitivities given in Table 3.…”
Section: Estimation Of E Essupporting
confidence: 64%
“…It was indicated that experimental values of electrostatic sensitivity of energetic materials depend on various factors such as granulometry and particle shape [36,37], moisture content [36], the molecular electronic properties [38], the configuration of electrodes [38][39][40], and the general structure of the circuit [36]. As seen in Table 4, the predicted electrostatic sensitivities for the compounds are consistent with their impact sensitivities given in Table 3.…”
Section: Estimation Of E Essupporting
confidence: 64%
“…[95].E ven though results from the RDAD instrument also correlate very well with the moleculars tructure of polynitro compounds [1,19,21,98,99] they cannot be taken as values of a" pure" (real) electric spark sensitivity.I ti si mportant that the semilogarithmicr elationship between the E ES values and dissociation energies DH(NÀN) in nitramines is directly proportional [19].T he relationship of the results from both these instruments (i.e. RDAD and ESZ KTTV) is representedb y ab roken-line [19] for nitramines and full lines for polynitro arenes [20].T he majority of published papers aboutp rediction of the electric spark sensitivity (see for example [98][99][100][101][102][103][104][105][106]) are basedo nt he results using the RDAD apparatus [21,95,[107][108][109][110][111].…”
Section: Electric Spark Sensitivitymentioning
confidence: 99%
“…Using the old RDAD instrument, Zeman et al [10][11][12][13] reported the electric spark sensitivity of a large set of nitramines and polynitroarenes. These data have been used in recent years for the development of predictive methods for nitramines [14][15][16][17][18][19] and polynitroarenes [20][21][22]. Furthermore, the reported electric spark sensitivities based on the output from RDAD instruments have also been correlated with detonation performance [12,[23][24][25][26], impact sensitivity [27,28], thermal stability [29][30][31][32][33], and shock sensitivity [34,35].…”
Section: Introductionmentioning
confidence: 99%